2019
DOI: 10.3390/nano9071016
|View full text |Cite
|
Sign up to set email alerts
|

Biological Responses of Onion-Shaped Carbon Nanoparticles

Abstract: Nanodiamonds are emerging as new nanoscale materials because of their chemical stability, excellent crystallinity, and unique optical properties. In this study, the structure of nanodiamonds was engineered to produce carbon nano-onion particles (CNOs) with multiple layers. Following a series of physicochemical characterizations of the CNOs, various evaluations for biological responses were conducted for potential biotechnological applications of the CNOs. The possibility of biological applications was first co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In a subsequent study, Jang and coworkers evaluated CNOs cytotoxicity toward human dermal fibroblasts (HDF), showing no cytotoxicity or increased secretion of cytokines (IL-2 and TNF-α) and only low ROS production. Since ROS are believed to be the major cause of carbon nanomaterials toxicity, these data suggest a good biocompatibility of CNOs with fibroblasts [96].…”
Section: In Vitro Studiesmentioning
confidence: 90%
“…In a subsequent study, Jang and coworkers evaluated CNOs cytotoxicity toward human dermal fibroblasts (HDF), showing no cytotoxicity or increased secretion of cytokines (IL-2 and TNF-α) and only low ROS production. Since ROS are believed to be the major cause of carbon nanomaterials toxicity, these data suggest a good biocompatibility of CNOs with fibroblasts [96].…”
Section: In Vitro Studiesmentioning
confidence: 90%
“…[419] CNOs were also shown to induce negligible systemic toxicity against 4T1 breast cancer cell lines and minimal hemolytic activity against blood cells, even at the maximum concentrations of 100 μg mL −1 (Figure 21a-f). [93] A study conducted by Jang et al [420] demonstrated the outstanding biocompatibility and non-toxicity of CNOs towards human cells at concentrations below 500 ng mL −1 . Amora et al [418] elucidated the possible biological impacts of benzoic-acid-functionalized CNOs on zebrafish development.…”
Section: Cytotoxicity Of Cnosmentioning
confidence: 99%
“…[ 93 ] A study conducted by Jang et al. [ 420 ] demonstrated the outstanding biocompatibility and non‐toxicity of CNOs towards human cells at concentrations below 500 ng mL −1 . Amora et al.…”
Section: Toxicity and Pharmacokinetics Of Nanocarbonsmentioning
confidence: 99%
“…A recent study discussed functional immune response in workers from 12 different U.S. facilities exhibiting generally low levels of exposure to CNTs or nanofibers [19]. However, recent studies with macrophages and fibroblasts exposed to graphene and carbon-based nano-onions, respectively, showed very low ROS generation and cytotoxicity [89,90]. These observations prompted investigators to suggest that cytotoxicity results may be influenced by additional contaminating factors, such as bacterial endotoxin, introduced during manufacturing [89].…”
Section: Carbon-based Nanomaterials Compositions and Applicationsmentioning
confidence: 99%
“…For example, Abraxane®, an FDA-approved NP formed by albumin with conjugated paclitaxel, dissolves into soluble complexes after intravenous injection [27]. The particles can then accumulate in tumors due to the EPR effect and can be transported across endothelial by binding to membrane protein gp60 [90]. Albumin serves as a delivery vehicle and allows Abraxane® to achieve a high response rate for treating breast and pancreatic cancer.…”
Section: Protein-based Liposomesmentioning
confidence: 99%